2020
DOI: 10.1111/sjop.12640
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of social support in the experience of work engagement in middle age: A Northern Finland Birth Cohort 1966 Study

Abstract: So far, the relationship between the various dimensions of social support and work engagement has not been widely examined in the literature. In this study, we examined the relationship of social support at work (from a colleague or supervisor) and social support in one’s private life (from a spouse, relative or friend) with various dimensions of work engagement (vigor, dedication and absorption). The participants (N = 5,259–5,376, 46 years‐old, 52.7% women) came from the Northern Finland Birth Cohort 1966 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 74 publications
3
17
0
2
Order By: Relevance
“…These results suggest that Mexican bank employees perceive high QWF as a direct driver of employee engagement. Previous studies support the results of the current research (Capri et al, 2017;Farndale & Murrer, 2015;Kiema-Junes et al, 2020;Sommer & Kulkarni, 2012). For example, Karatepe et al (2014) found that employee responsibility with direct customer contact is a challenging factor that drives engagement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results suggest that Mexican bank employees perceive high QWF as a direct driver of employee engagement. Previous studies support the results of the current research (Capri et al, 2017;Farndale & Murrer, 2015;Kiema-Junes et al, 2020;Sommer & Kulkarni, 2012). For example, Karatepe et al (2014) found that employee responsibility with direct customer contact is a challenging factor that drives engagement.…”
Section: Discussionsupporting
confidence: 86%
“…Working with friendly people enables the strengthening of good relationships among co-workers (Alegre, Mas-Machuca, & Berbegal-Mirabent, 2016), increasing participation (Lambert et al, 2016) through teamwork (Alegre et al, 2016). The relationship between social support and WE has recently been proven; for example, the results of Kiema-Junes et al (2020) showed that social support received from supervisors, co-workers and family influenced WE. In particular, social support was the strongest predictor for employee dedication and determination.…”
Section: Quality In Work Factors and Work Engagementmentioning
confidence: 99%
“…Trabajar con personas amigables permite fortalecer las buenas relaciones entre compañeros (Alegre, Mas-Machuca, & Berbegal-Mirabent, 2016) aumentando la participación (Lambert et al, 2016) a través del trabajo en equipo (Alegre et al, 2016). La relación entre el apoyo social y el CL ha sido validada recientemente, por ejemplo, los resultados de Kiema-Junes et al (2020) mostraron que el apoyo social recibido de los supervisores, compañeros y familia influyeron en el CL, particularmente, el apoyo social fue el predictor más fuerte para la dedicación y el vigor de los empleados. Similarmente, los hallazgos de Nasurdin, Ling y Khan (2018) mostraron que las percepciones de apoyo del supervisor fueron el predictor más fuerte del CL, además, el apoyo recibido por los compañeros y la organización también fueron determinantes importantes del CL.…”
Section: Calidad En Los Factores Del Trabajo Y Compromiso Laboralunclassified
“…Estos resultados sugieren que los empleados bancarios mexicanos perciben una alta CFT que propicia de manera directa el compromiso de sus colaboradores. Los estudios previos soportan los resultados de la investigación actual (Capri et al, 2017;Farndale & Murrer, 2015;Kiema-Junes et al, 2020;Sommer & Kulkarni, 2012). Por ejemplo, Karatepe et al (2014) encontraron que la responsabilidad de los empleados con contacto directo con los clientes es un factor desafiante que impulsa el compromiso.…”
Section: Discusión Y Conclusiónunclassified
“…Research on the influence of workplace social support has focused on evaluating the impact of support received from various sources, typically supervisors and colleagues, to foster work engagement. For example, Kiema-Junes et al (2020) reported that high social support at work was associated with higher total work engagement, higher vigor, higher dedication, and higher absorption in Northern Finland. The study considered two types of social support, namely supervisory and collegial, and it discovered a common link: both promoted work engagement.…”
Section: Workplace Social Support and Work Engagementmentioning
confidence: 99%